Hypercrosslinked phenothiazine-based polymers as high redox potential organic cathode materials for lithium-ion batteries - Zhang, Ying; Gao, Panpan; Guo, Xinya; Chen, Han; Zhang, Ruiqiang; Du, Ya; Wang, Baofeng; Yang, Haishen (RSC advances, 2020)
Organic cathode materials have been demonstrated to be highly promising sustainable cathode materials for rechargeable lithium-ion batteries. However, the low redox potentials, low electrical conductivity, and the undesirable dissolution in organic electrolytes greatly limit their applications. Herein, two insoluble hypercrosslinked porous conductive polymers with phenothiazine motifs, HPEPT and HPPT , were successfully accomplished with high and stable discharge potentials at 3.65 and 3.48 V versus Li/Li + . HPEPT and HPPT with good electrical conductivity exhibited outstanding rate capabilities (up to 800 mA g −1 ) even at a high mass loading up to 70 wt%. This study shows that excellent organic cathode materials could be achieved readily through this prudent design. Hypercrosslinked conductive polymers with phenothiazine motifs were achieved and studied as organic cathode materials, exhibiting excellent electrochemical performance.